2022
DOI: 10.1021/jacs.2c02538
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Core-Shell Cu-Ru, Cu-Rh, and Cu-Ir Nanoparticles

Abstract: Optimizing the use of expensive precious metals is critical to developing sustainable and low-cost processes for heterogeneous catalysis or electrochemistry. Here, we report a synthesis method that yields core-shell Cu-Ru, Cu-Rh, and Cu-Ir nanoparticles with the platinum-group metals segregated on the surface. The synthesis of Cu-Ru, Cu-Rh, and Cu-Ir particles allows maximization of the surface area of these metals and improves catalytic performance. Furthermore, the Cu core can be selectively etched to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 55 publications
6
31
0
Order By: Relevance
“…The Arrhenius plot for pure Cu particles in a previous work showed high activity for Cu at high temperatures, in the 230-280 °C range. 32 This is also consistent with previous publications as Cu is not considered an efficient catalyst for CO oxidation. 41,42,43 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The Arrhenius plot for pure Cu particles in a previous work showed high activity for Cu at high temperatures, in the 230-280 °C range. 32 This is also consistent with previous publications as Cu is not considered an efficient catalyst for CO oxidation. 41,42,43 .…”
Section: Resultssupporting
confidence: 93%
“…This has been shown in other publications about bimetallic particles with Cu. 32,21 Upon exposure to oxygen at high temperatures, Cu migrates to the surface and form Cu oxide, which covers the second transition metals. In our case, it seems that the Pt-rich surface prevented migration of Cu to the surface, which allowed Cu-Pt particles to remain active after the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis with metal carbonyl can tune the shape of nanoparticles and yield spheres or cubes, depending on the quantity of precursors and the reaction temperature . Finally, the amount of capping agent added to the solution, such as oleylamine, and the reaction temperature, are crucial to control the size and composition of nanoparticles. ,, Previous publications have reported promising properties of Pt-based bimetallic particles. For instance, it has been demonstrated that core–shell Pt 3 Pb–Pt nanoparticles are highly efficient for formic acid oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium (Rh) is the nearest metal to Platinum (Pt) located at the vertex of volcano plot with small Gibbs free energy 13 , and has been demonstrated have excellent catalytic stability. Distinct from bulk metals, the intrinsic activity of the catalyst has been demonstrated to strongly depend on the size, the exposed defects, and the supports [14][15][16][17][18][19] . As an important traditional metal support, carbon materials show great application value in catalysis field, therefore, carbon materials are considered as the key component of highperformance catalysts [20][21][22] .…”
mentioning
confidence: 99%